Labour cost and employment across euro area countries and sectors - Beatrice Pierluigi; Moreno Roma (European Central Bank (ECB), 2008)
This paper studies the role of wage moderation and labour and product market regulation for employment creation. To this end, labour demand estimates are presented for the five largest euro area countries at the aggregate level and for three macro sectors: manufacturing, construction and services. Estimates are carried out for individual countries as well as for the pooled group of countries. This paper shows that labour cost moderation generally helps employment creation, notwithstanding the fact that elasticities of employment to labour costs vary across the countries and sectors analysed. It also shows that some key institutional/structural variables add to the explanation of labour demand developments. In particular, in some countries and sectors, our results point to a negative link between employment growth, the unemployment benefit replacement rate and product market regulation.
Keywords: E24; J23; J30; C22; C23; 330; labour cost; labour demand; panel estimates; Arbeitskosten; Lohnniveau; Arbeitsnachfrage; Industrie; Bauwirtschaft; Dienstleistungssektor; Arbeitsmarktpolitik; Eurozone; EU-Staaten